Assessment IS learning: developing a student‐centred approach for assessment in Higher Education - Stephen Rutherford; Connie Pritchard; Nigel Francis (FEBS Open Bio)
Assessment and the associated feedback from those assessments are powerful factors in the development of students' learning. We have seen a shift within the Higher Education sector to conceptualise assessment as being more than summative assessment ‘of’ learning. Instead, there has been a greater emphasis on assessment ‘as’ learning, or assessment ‘for’ learning, through the enhanced use of formative assessments. Centralising assessment within the learning process highlights that assessment IS learning and cannot be separated from other elements of the learning process. In particular, assessment has a vital role to play in the development of students' self‐regulated learning skills and the development of independence in learners. However, for assessments to effectively support learning, they need to be meaningful, engaging, well‐integrated into the learning activities and ‘student‐focused’. Placing student skills development and personal development at the centre of assessment design has the potential to empower students through assessment. This review focuses on the potential of assessment to support student learning and development, using the ‘Equity, Agency, Transparency’ (‘EAT’) framework as a lens for effective assessment and feedback practices. We suggest ways in which we can make our assessment and feedback practices more inclusive, meaningful and authentic to the students' learning needs.